I need to solve this for b
Here's what I got so far:
a(a-b) = 3s(3s+b)
a^2 - ab = 9s^2 + 3sb
divide it all by a
a^2/ a - ab/a = 9s^2/a + 3sb/a
gives
a - b = 9s^s/a + 3sb/a
-b = 9s^s/a + 3sb/a -a
....not sure what to do about that b in 3sb?
Thanks
The idea is to isolate b alone by itself in the lefthand side.
After your second line, collect all the b-terms at the lefthand side, factor out the b, etc,
Umm, let me continue...
a(a-b) = 3s(3s+b)
a^2 - ab = 9s^2 + 3sb
-ab -3sb = 9s^2 -a^2
b(-a -3s) = 9s^2 -a^2
b(-(3s +a)) = (3s +a)(3s -a)
Divide both sides by -(3s +a),
b = -(3s -a)
b = a -3s ---------------------------answer.